Metaphorical Conceptualization and its Cultural Foundations in Persian Literature (Case Study: The Metaphor of Love is War) - Jahandoost Sabzalipour; Raziye roosami juryabi (مطالعات زبانی و بلاغی)
Metaphor plays an important role in the conceptualization and understanding of human, and nowadays it is considered as one of the tools of the human`s cognitive system. By studying metaphors in any languages we can find a way to the minds of the users of that language. It's hard to believe that Love is like a war, because love is spiritual, emotional and desirable for all individuals and nations, but there is such a metaphor in Persian language and literature. The purpose of this article is reading and Extraction the metaphors of love in two literary works “The Ghazlites” of Attar and Iraqi. The results of this article Prove that Persian language uses words of the battlefield to introduce love. Replacement and non-abstraction in this field, reflects the hidden ideas of poets, and shows that these maps follow the conceptual metaphor of "love is human". This metaphor is so high frequency in Persian literature. It seems that without the help of war, we cannot talk about love.